Exposure to a combination of heat and hyperoxia during cycling at submaximal intensity does not alter thermoregulatory responses - Zinner, C; Krueger, M; Reed, JL; Kohl-Bareis, M; Holmberg, H-C; Sperlich, B (Biology of Sport, 2016)
In this study, we tested the hypothesis that breathing hyperoxic air (FinO2 = 0.40) while exercising in a hot environment exerts negative effects on the total tissue level of haemoglobin concentration (tHb); core (Tcore) and skin (Tskin) temperatures; muscle activity; heart rate; blood concentration of lactate; pH; partial pressure of oxygen (PaO2) and carbon dioxide; arterial oxygen saturation (SaO2); and perceptual responses. Ten well-trained male athletes cycled at submaximal intensity at 21°C or 33°C in randomized order: first for 20 min while breathing normal air (FinO2 = 0.21) and then 10 min with FinO2 = 0.40 (HOX). At both temperatures, SaO2 and PaO2, but not tHb, were increased by HOX. Tskin and perception of exertion and thermal discomfort were higher at 33°C than 21°C (p 0.07). Blood lactate and heart rate were higher at 33°C than 21°C. In conclusion, during 30 min of submaximal cycling at 21°C or 33°C, Tcore, Tskin and Tbody, tHb, muscle activity and ratings of perceived exertion and thermal discomfort were the same under normoxic and hyperoxic conditions. Accordingly, breathing hyperoxic air (FinO2 = 0.40) did not affect thermoregulation under these conditions.